ANALISIS PROJEK PENGUATAN PROFIL PELAJAR PANCASILA PADA TEMA GAYA HIDUP BERKELANJUTAN BERBASIS ECOPRINT TERHADAP DIMENSI KREATIF PESERTA DIDIK KELAS V SD NEGERI 1 WINONG TAHUN PELAJARAN 2024/ 2025 - Muflikah Nur Hidayah; Anggit Grahito Wicaksono; Sarafuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This research focuses on analyzing the implementation of the Pancasila Student Profile Strengthening Project (P5) using an ecoprint approach at SD Negeri 1 Winong. The objectives are to examine how this project develops the creativity of fifth-grade students, identify the obstacles encountered during its execution, and evaluate its specific impact on the creative dimension of the students. The research method is descriptive qualitative. The subjects include the school principal, a fifth-grade teacher, and three students who served as key informants. The object of the study is the application of ecoprint itself. Data was collected through observation, interviews, and documentation, then analyzed using source data triangulation, which involves data reduction, data presentation, and conclusion drawing. The findings indicate that the ecoprint-based P5 Project successfully stimulated students' creativity, self-reliance, and collaborative spirit (gotong-royong). However, some technical challenges were identified, such as the limited availability of quality fabric and the difficulty students faced in the leaf-pounding process, which could damage the cloth. Despite these constraints, the project demonstrated a significant positive impact by stimulating innovative ideas and fostering student enthusiasm through hands-on practice. Collaboration among teachers, students, and parents was a key factor in its success. The evaluation suggests that improvements in material provision and stronger collaborative support could further optimize the project. Overall, the ecoprint project proved to be an effective, relevant, and meaningful learning method.